Percutaneous cryoablation for desmoid fibromatosis: initial experience at a UK centre. Issue 10 (October 2022) - Johnston, E.W.; Alves, A.; Messiou, C.; Napolitano, A.; Strauss, D.; Hayes, A.; Smith, M.J.; Benson, C.; Jones, R.L.; Gennatas, S.; Fotiadis, N.
Abstract : AIM: To report the first UK experience of cryoablation in desmoid fibromatosis (DF) with particular focus on technique, safety, and efficacy. MATERIALS AND METHODS: Patients were selected at multidisciplinary tumour board meetings at a specialist cancer hospital. Radiation dose, procedure duration, and number of cryoprobes were compared for small versus large tumours (>10 cm long axis). Response at magnetic resonance imaging (MRI) was evaluated using different criteria, and percentage agreement with clinical response as assessed in oncology clinic calculated. RESULTS: Thirteen procedures were performed in 10 patients (eight women, median age 51 years, IQR 42–69 years) between February 2019 and August 2021. Procedures for large tumours had higher radiation dose (2, 012 ± 1, 012 versus 1, 076 ± 519 mGy·cm, p= 0.048) used more cryoprobes (13 ± 7 versus 4 ± 2, p= 0.009), and were more likely to have residual unablated tumour (38 ± 37% versus 7.5 ± 10%, p= 0.045). Adverse events were minor apart from one transient radial nerve palsy. Eight of 10 patients had symptomatic benefit at clinical follow-up (median 353 days, IQR 86–796 days), and three started systemic therapy mean 393 days later. All patients who had complete ablation demonstrated symptomatic response, with no instances of repeat treatment, recurrence, or need for systemic therapy during the study period. All progression occurred outside ablation zones. CONCLUSION: Cryoablation for symptomatic DF is a reproducible technique with low, transient toxicity, where one or two treatments can achieve a meaningful response. Where possible, the ablation ice ball should fully cover DF tumours. Highlights: Cryoablation for desmoid fibromatosis has been reproduced at a UK centre. Our results show few adverse events and high levels of symptomatic benefit. Tumour volume seems to better reflect symptomatic response than long-axis measurement.